Ethnic Groups in Motion : Economic Competition and Migration in Multi-Ethnic States. - Bookman, Milica Z. (Routledge studies in nationalism and ethnicity., 2012)
This title focuses on one aspect of migration, namely its ethnic competition. Rather than observe population movements in general, the study is limited to the movements of specific ethnic groups. It explores the role played by ethnicity in determining which groups move and which groups stay.